Simplex Lattice Approach to Optimize Yields of Light Oil Products from Catalytic Cracking of Bio-Oil with Mixed Catalysts - Chawannat Jaroenkhasemmeesuk (2018)
© 2017, Copyright © Taylor & Francis Group, LLC. Bio-oil is a potential product from the fast pyrolysis of biomass. However, it should be upgraded before being used in subsequent applications and corrosion prevention. In this work, crude bio-oil from fast pyrolysis of Jatropha curcas residues, which has many long-chain compounds, and a high content of carboxylic acid, was catalytically upgraded over mechanically mixed catalysts (normal ZSM-5 and Y-Re-16) in a fixed-bed reactor. The effects of the key parameters on the yields of light oil products were analyzed, including cracking temperature (350–500°C), reaction time (15–60 min), catalyst loading (10–25%), and mixture ratio between Y-Re-16 and ZSM-5 (10–70%). Experimental test cases were based on a simplex lattice design. The gas chromatograph-mass spectrometer (GC-MS) analysis showed that the catalytic cracking of crude bio-oil using mixed catalysts resulted in the successful formation of short-chain acid methyls. The employed analytical fit of the experimental data gave R2and the adjusted R2of 0.902 and 0.843, respectively. The optimized operation conditions to produce aliphatic hydrocarbons from mechanically mixed catalysts were found to be at 400°C, 15 min of reaction time, 15% of catalyst loading, and a mixture ratio of about 1:5.